2015
DOI: 10.1371/journal.pone.0145884
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Chromosomal Island SpyCIM1 from Streptococcus pyogenes Strain SF370 Reverses the Mutator Phenotype and Alters Global Transcription

Abstract: Streptococcus pyogenes chromosomal island M1 (SpyCIM1) integrates by site-specific recombination into the 5’ end of DNA mismatch repair (MMR) gene mutL in strain SF370SmR, blocking transcription of it and the downstream operon genes. During exponential growth, SpyCIM1 excises from the chromosome and replicates as an episome, restoring mutL transcription. This process is reversed in stationary phase with SpyCIM1 re-integrating into mutL, returning the cells to a mutator phenotype. Here we show that elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…However, all resulting mutants (> 500 CFU) were Sm R / Kan R , suggesting a rate of recombination, gene conversion or mutation in the rpsL WT gene of the Janus cassette was significantly higher than the rate of loss of SpyCIM1 [ 46 ]. This confirmed previous results that SpyCIM1 was difficult to cure from SF370 [ 5 , 7 , 58 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, all resulting mutants (> 500 CFU) were Sm R / Kan R , suggesting a rate of recombination, gene conversion or mutation in the rpsL WT gene of the Janus cassette was significantly higher than the rate of loss of SpyCIM1 [ 46 ]. This confirmed previous results that SpyCIM1 was difficult to cure from SF370 [ 5 , 7 , 58 ].…”
Section: Resultssupporting
confidence: 92%
“…pyogenes (or potentially other bacteria) that differ solely in phage content. Such KO strains will be useful tools to study the dynamics of phage lysogeny, the role phage play in both bacterial virulence and the regulation of chromosomal genes [ 58 ], and can provide insight into the evolution of streptococcal pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…A mutator phenotype was found in a serotype M1 GAS strain, SF370, where a defective phage, SpyClM1, may exist as lysogens or episomes depending on the growth status (36,43). The switching status of the phage altered the global transcription profile, probably by controlling the regulation of the DNA mismatch repair (MMR) operon, thus facilitating alternative adaptation for survival of the bacteria in host cells (44). In this regard, it is possible that the phages in the strain studied here also have evolved to influence virulence at the gene regulation level in addition to the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…These isogenic pairs were M1 strains SF370 and SF370ΔSpyCIM1 and M6 strains MGAS10395 and MGAS10395ΔSpyCIM6. In SF370, our laboratory has demonstrated that SpyCIM1 is involved in altering global transcription (50). Genes upregulated in the presence of SpyCIM1 include emm and capsule gene hasB.…”
Section: Discussionmentioning
confidence: 99%